ANALISIS PERBEDAAN METODE PEMBELAJARAN KONVENSIONAL DAN ACTIVE LEARNING MAHASISWA AKUNTANSI UNIVERSITAS CIPUTRA - Gunawan, Sherley; Santoso, Eko Budi; Mastan, Stanislaus Adnanto (Media Akuntansi dan Perpajakan Indonesia, 2019)
The purpose of this research is to find the difference between conventionallearning method and active learning on accounting student CiputraUniversity batch 2018. Control method use PowerPoint and the experimentuse reading guide and think group share. This research uses quasi experimentwith post-test control group design, so it’s just look at the final result of thetwo classes. This research divides the respondents into two classes, 20 studentson control class and 20 students on experiments class. This researchusing data from post-test by questionnaire with 10 questions multiple choice.The data analysis in this research use T-Test to see the difference betweenconventional learning method and active learning. The results of this researchshow that there is the differences in conventional learning methoduse PowerPoint and the active learning use reading guide and think groupshare with the average value of 82.50 for experiment class and 62.50 forcontrol class and the significance value is 0.003 < 0.05 so that H1 is acceptedand H0 is rejected.